Carta de Luis Muñoz Rivera a Roberto H. Todd - Todd, Roberto H.; Muñoz Rivera, Luis (My University, 1913)
Carta relacionada a excusas a Roberto H. Todd por no poder asistir a un compromiso.
Keywords: Muñoz Rivera, Luis--Correspondence.; Muñoz Rivera, Luis--Correspondencia.; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.